Role of Hydrogen Sulfide in the Endocrine System - Chen, Hao-Jie; Ngowi, Ebenezeri Erasto; Qian, Lei; Li, Tao; Qin, Yang-Zhe; Zhou, Jing-Jing; Li, Ke; Ji, Xin-Ying; Wu, Dong-Dong (Frontiers in Endocrinology, 2021)
Hydrogen sulfide (H2S), as one of the three known gaseous signal transduction molecules in organisms, has attracted a surging amount of attention. H2S is involved in a variety of physiological and pathological processes in the body, such as dilating blood vessels (regulating blood pressure), protecting tissue from ischemia-reperfusion injury, anti-inflammation, carcinogenesis, or inhibition of cancer, as well as acting on the hypothalamus and pancreas to regulate hormonal metabolism. The change of H2S concentration is related to a variety of endocrine disorders, and the change of hormone concentration also affects the synthesis of H2S. Understanding the effect of biosynthesis and the concentration of H2S on the endocrine system is useful to develop drugs for the treatment of hypertension, diabetes, and other diseases.